(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Contracting companies play a prominent role today in economic activity, due to their contribution to the implementation of major construction projects which together constitute the infrastructure of society. Most construction projects also suffer from exceeding the time and cost specified and planned for the completion of the project, and this comes for several reasons, including the work environment, country conditions, The method of managing project costs and the techniques used in its implementation Accordingly, the concepts of lean construction came, which help in addressing the causes of waste, both in time and cost, in addition to the fact that project management needs techniques that are useful in controlling the control and management of project costs at every stage of implementation, In this paper, an earned value management model was used to control project cost and detect deviations in a timely manner This study was also used to address deviations in cost or time with lean construction techniques and to identify their causes in order to rationalize costs and improve the indicators of the project control model. As well as diagnosing waste areas and finding solutions in possible ways through the use of lean construction tools, represented by the value flow map, standard work, continuous improvement, and total quality management. Where the study reached an analysis of selected stages and tasks of the project to reach the sources of waste and try to cancel unnecessary activities and find possible ways to implement in order to improve the construction work and complete the projects on time and within their planned cost, taking into account the maintenance and upgrading of the quality level.